ADVANCING THE PRODUCTION OF VIRAL VECTORS FOR CAR-T CELL THERAPY IN KAZAKHSTAN - Syzdykova, L.R.; Keyer , V.V.; Arsienko , R.Y.; Inirbay , B.K.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2023)
Therapy of hematological tumors with chimeric antigen receptor-expressing T-cells (CAR-T) is a recent technology which holds promise to become the most significant achievement in oncohematology over the past 20 years. One aspect of the clinically applied CAR-T technology is that the process of production of CAR+ cells requires viral vectors which are used to deliver the CAR gene in T lymphocytes. At present the production of CAR-T therapy depends on the availability of packaged lentiviral or retroviral vectors. There is a worldwide deficiency in a production capacity to produce CAR vectors, and clinical-use vectors are not sold as off-the-shelf products. At the National center for biotechnology the CAR receptor was assembled and this CAR targets the CD19 antigen which is a marker of tumor cells of the B-cell origin, lentiviral vectors were constructed. Studies on the production of packaged vectors were conducted at which three types of transfection reagents were compared for efficiency, in terms of the produced functional titers. A method was developed to measure functional titers using flow cytometry. High titers of the packaged vectors were obtained. As the CAR-T is effective for treatment of patients after failure of traditional therapy, with relapse or refractory disease, all works on transfer of the CAR-T technology to Kazakhstan are of life importance to the patients with blood cancers in the country. The results underscore a necessity to organize a full production process to produce CAR vectors for clinical use and therapeutic cells for the CAR-T therapy at the NCB.